Impact of COVID-19 on the Reported Case Volume of Orthopaedic Sports Medicine Fellows in the United States. Issue 2 (14th February 2023) - Silvestre, Jason; Nelson, Charles L.; Kelly, John D.; Thompson, Terry L.
Background: The impact of the coronavirus 2019 (COVID-19) pandemic on reported case volume during orthopaedic sports medicine fellowship training remains poorly understood from a national perspective. Hypothesis: It was hypothesized that reported case volume during orthopaedic sports medicine fellowship training would decrease during the 2019-2020 academic year, which corresponded to the COVID-19 outbreak. It was also hypothesized that there would be a subsequent rebound in case volume during the 2020-2021 academic year. Study Design: Cohort study. Methods: Reported mean case volumes were extracted for 4 academic years (2017-2018, 2018-2019, 2019-2020, and 2020-2021), and year-over-year percentage changes were calculated. Parametric tests were used for interyear comparisons. Results: There was a 7% decrease in mean ± SD case volume between the 2018-2019 and 2019-2020 academic years (339 ± 123 vs 316 ± 108; P = .042). Case categories with the greatest percentage declines were foot and ankle (–20%), knee instability (–11%), meniscus (–8%), and glenohumeral instability (–7%). There was a 13% year-over-year increase in case volume between the 2019-2020 and 2020-2021 academic years (316 ± 108 vs 357 ± 117; P < .001). Conclusion: There was a slight decrease in total orthopaedic sports medicine case volume during the 2019-2020 academic year, corresponding to widespread lockdowns during the COVID-19 outbreak. Certain case categories experienced the greatest negative impact. Results from this study may inform accrediting bodies and surgical educators on the impact of future disruptions to health care delivery.